KUALITAS DENDENG GILING AYAM AFKIR YANG DIBERI CAMPURAN JANTUNG PISANG DAN KELAPA PARUT - Susana Serlince Harry; Bastari Sabtu; Gemini E.M Malelak (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2019)
The aimed of this experiment was to examine the effect of adding banana flower and grated coconut on culled chiken dendeng (thin dry meat). Experiment design used was completely randomized design (CRD) 4 treatments and 3 replication. The treatments were: D0: culled chiken only (as control), D1: culled laying chiken + banana flower 20% (w/w) + grated coconut 10% (w/w); D2: culled laying chiken + banana flower 15% (w/w) + grated coconut 15% (w/w); D3: culled laying chiken + banana flower 10% (w/w) + grated coconut 20% (w/w). Variables measured were: aroma, color, taste, the content of water, fat and protein. Analysis result showed that treatment was highly significant affected (P< 0.01) The color and taste wasnot effected by treatments. Conclution, the addition of banana flower and coconut grated caused the aroma score decreased but did not decrease the color score and taste score of culled chiken dendeng . The addition of more levels of banana flower from grated coconut caused an increase in culled chiken dendeng water content, the addition of grated coconut content from the banana flower caused an increase in fat levels but decreased protein content.